2022
DOI: 10.1021/acs.jpcb.2c05774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Branching on Mutual Solubility of Alkane–CO2 Systems by Molecular Simulations

Abstract: Mutual solubilities of hydrocarbon–CO2 systems are important in a broad range of applications. Experimental data and theoretical understanding of phase behavior of large hydrocarbon molecules and CO2 are limited. This is especially true in relation to the molecular structure of hydrocarbons when the carbon number exceeds 12. In this work, the continuous fractional component Gibbs ensemble Monte Carlo simulations are used to investigate mutual solubility of different alkane and CO2 systems and the molecular str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In the eHeX from this work and in the HeX from Perronace et al, a united-atom model has been used as the force field. The use of LB combining rules could be inadequate to represent united-atom models, and an adjustable parameter for the cross-energy parameter may be required. , This could be the reason for a systematic deviation from experimental data. However, based on the thermodynamic factor, C 5 –C 10 behaves as an ideal liquid, and the intermolecular interactions should not be as relevant.…”
Section: Resultsmentioning
confidence: 99%
“…In the eHeX from this work and in the HeX from Perronace et al, a united-atom model has been used as the force field. The use of LB combining rules could be inadequate to represent united-atom models, and an adjustable parameter for the cross-energy parameter may be required. , This could be the reason for a systematic deviation from experimental data. However, based on the thermodynamic factor, C 5 –C 10 behaves as an ideal liquid, and the intermolecular interactions should not be as relevant.…”
Section: Resultsmentioning
confidence: 99%
“…Nan et al [122,123] investigated how alcohols with different tail lengths (C 2 OH-C 16 OH) and concentrations affect the water-AOT-scCO 2 interface system through MD simulations. Kobayashi et al [124] discussed the mutual solubility of heavy n-alkanes (typically, n-decane, n-hexadecane, n-eicosane) and their structural isomers in CO 2 -rich and hydrocarbon-rich phases using continuous fractional component Gibbs integrated Monte Carlo simulations and suggested that the improvement of solubility is due to a higher coordination number of CO 2 for methyl (CH 3 ) rather than for methylene (CH 2 ) groups.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%